Legitimising a 'Zombie idea': childhood vaccines and autism. (30th September 2020) - Rizzi, M; Attwell, K; Casigliani, V; Taylor, J; Quattrone, F; Lopalco, P
Abstract: Background: In June 2017 the Italian government made childhood vaccination mandatory following a drop in immunization rates. In the years preceding, two court judgments affirmed a causal link between vaccines and autism. Studies have linked these decisions to internet searches about vaccine-autism, the popularity of 'no-vax' theories, and drops in immunization rates. This paper provides an in-depth case study of both decisions and their impact. Methods: We use a synthetic research design reliant on: (i) a systematic collection of primary sources (publicly available and obtained via official access to information requests); (ii) interviews with key actors prominently involved in the two cases or privy to the Italian vaccine-injury compensation regime (iii) a systematic analysis of media coverage. Results: Circumstantial and systemic flaws enabled these decisions. Poor trial strategies, insufficient resources and laborious communication practices between arms of government were facilitators. Lack of awareness of the social sensitivity of vaccine issues, underestimation of the phenomenon of vaccine hesitancy, and a tendency to 'think in silos' informed the lack of attention dedicated to the cases. The decisions created false expectations of economic benefits and vindication for families with autistic children, resulting in increased litigation. Systemic flaws exist in the process of appointment of expert consultants acting for the court leading to judicial reliance on false data. Conclusions: Lessons learned include greater levels of attention to vaccine cases by the administration and a matured attitude of adjudicating bodies. Two issues remain: (i) the inability of government lawyers to disseminate positive results to counteract unfounded narratives; (ii) flaws in the process of appointing expert consultants advising courts, which remains focused on the fiduciary nature of the relationship, rather than scientific authority. Key messages: The Milan and Rimini decisions that directly affected vaccine governance stemmed from a combination of circumstantial decision-making and systemic flaws that still lurk in public health governance. Strategic decision-making that overlooks lower levels of the adjudicative system can lead to significant public health consequences as courts of law and courts of public opinion obey different logics.